What have we learned from Turkish familial hypercholesterolemia registries (A-HIT1 and A-HIT2)? - Kayikcioglu, Meral; Tokgozoglu, Lale; Dogan, Volkan; Ceyhan, Ceyhun; Tuncez, Abdullah; Kutlu, Merih; Can, Levent H. (Elsevier Ireland Ltd, 2018)
Background and aims: Familial hypercholesterolemia (FH) is a common genetic disease of high-level cholesterol leading to premature atherosclerosis. One of the key aspects to overcome FH burden is the generation of largescale reliable data in terms of registries. This manuscript underlines the important results of nation-wide Turkish FH registries (A-HIT1 and A-HIT2). Methods: A-HIT1 is a survey of homozygous FH patients undergoing low density lipoprotein (LDL) apheresis (LA). A-HIT2 is a registry of adult FH patients (homozygous and heterozygous) admitted to outpatient clinics. Both registries used clinical diagnosis of FH. Results: A-HIT1 evaluated 88 patients (27 +/- 11 years, 41 women) in 19 centers. All patients were receiving regular LA. There was a 7.37 +/- 7.1-year delay between diagnosis and initiation of LA. LDL-cholesterol levels reached the target only in 5 cases. Mean frequency of apheresis sessions was 19 +/- 13 days. None of the centers had a standardized approach for LA. Mean frequency of apheresis sessions was every 19 +/- 13 (7-90) days. Only 2 centers were aware of the target LDL levels. A-HIT2 enrolled 1071 FH patients (53 +/- 8 years, 606 women) from 31 outpatients clinics specialized in cardiology (27), internal medicine (1), and endocrinology (3); 96.4% were heterozygous. 459 patients were on statin treatment. LDL targets were attained in 23 patients (2.1% of the whole population, 5% receiving statin) on treatment. However, 66% of statin-receiving patients were on intense doses of statins. Awareness of FH was 9.5% in the whole patient population. Conclusions: The first nationwide FH registries revealed that FH is still undertreated even in specialized centers in Turkey. Additional effective treatment regiments are urgently needed.
Keywords: Familial hypercholesterolemia; Turkey; Registry